1994
DOI: 10.1021/bi00193a023
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Kinetic Parameters of Escherichia coli Leader Peptidase Activity Using a Continuous Assay: The pH Dependence and Time-Dependent Inhibition by .beta.-Lactams Are Consistent with a Novel Serine Protease Mechanism

Abstract: Bacterial leader peptidase (LPase) is a potential target for the development of novel anti-infective agents, but to data only peptides based upon natural macromolecular substrates have been reported as inhibitors. In this work is described a continuous assay for Escherichia coli LPase activity, based upon Ac-WSASALAKI-AMC (I) as the substrate, that can be monitored either spectrophotometrically or spectrofluorometrically. The LPase reaction is coupled to the liberation of AMC (aminomethylcoumarin) via a nonspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 64 publications
1
32
0
Order By: Relevance
“…5). In addition to their role in blocking transpeptidases responsible for cross-linking peptidoglycan, ␤-lactam antibiotics also inhibit signal peptidase I (22). As a result, ␤-lactams inhibit the proteolytic processing of autotransporters such as PmpD, presumably by preventing their release from the cytoplasmic membrane and transport to the outer membrane (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). In addition to their role in blocking transpeptidases responsible for cross-linking peptidoglycan, ␤-lactam antibiotics also inhibit signal peptidase I (22). As a result, ␤-lactams inhibit the proteolytic processing of autotransporters such as PmpD, presumably by preventing their release from the cytoplasmic membrane and transport to the outer membrane (20).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that the translocation of PmpD to the bacterial cell surface is inhibited by ␤-lactam antibiotics (20), presumably as a result of inhibition of signal peptidase I activity at the cytoplasmic membrane (22). In Chlamydia-infected cells, low-level ␤-lactam antibiotic treatment prevents bacterial division, leading to the formation of enlarged RBs that morphologically resemble persistent forms (26).…”
Section: Identification Of Pls Proteins Ct049 and Ct050mentioning
confidence: 99%
“…The latter pre-proteins are not cleaved in E. coli and act as competitive inhibitors of signal peptidase. Recently, after a long search, two pharmaceutical companies have discovered that certain p-lactam compounds inhibit the E. coli signal peptidase (Kuo et al, 1994;Allsop et al, 1995). The best inhibitor reported is a 5s penem derivative, which has an I.C.…”
Section: Substrates and Inhibitorsmentioning
confidence: 99%
“…The first effective synthetic signal peptidase inhibitors to be discovered were described by Kuo and collegues in 1994 (25). They showed that ␤-lactam analogs inhibited E. coli SPase.…”
mentioning
confidence: 99%